Interaction between T Cells and Endothelial Cells: Insights into Immune Response and Vascular Health among Children - Hawsawi, Yousef; Alotaibi, Shmoukh; Alanazi, Badi; Alsofyani, Abeer; Bukhari, Talat; Alanazi, Abdulmajeed; Alanazi, Wafa; Alanazi, Majed; Alanazi, Faisal M.; Alanazi, Meaad; Alanazi, Aiysha; Alanazi, Fahad; et al. (International Journal of Child Health and Nutrition, 2024)
The functioning of T cells, key players in the immune response, is inherently influenced by specific nutrients. Understanding how dietary factors influence T cell function is pivotal in the context of child health. Eendothelial cell antigen presentation to T cells influences the outcome of several immune system functions. However, the consequences of these interactions are still discussed, with different responses observed depending on the phenotype and functional reactivity of both cells. Relating our findings to specific nutrition-related diseases in children, such as obesity, diabetes, and cardiovascular issues, establishes a direct link between T cell-endothelium interactions and pediatric health outcomes. The role of nutritional interventions extends beyond meeting basic dietary needs; it plays a dynamic role in shaping immune responses in children. Recognizing the interconnectedness of nutrition and immunology allows for developing targeted strategies. In this study, we find a close relationship between T lymphocytes (CTL) and endothelium, which is required and important for proliferation and differentiation to determine the size of the cell mass in the circulation. With an eye towards therapeutic opportunities, this review discusses in detail the link between both, how they are each activated, their substrates, and their regulation, and maps out how they interact.